Smallholder dairy farms in the mixed mountain farming systems: A case of the Uttaranchal Hills - SINGH, VIR; TULACHAN, PRADEEP M; PARTAP, TEJ (The Indian Journal of Animal Sciences, 2014)
This paper attempts to characterise the smallholder dairy farms in the typical crop-livestock mixed mountain farming< systems in the Hills of Uttaranchal. An inventory from smallholders in 12 villages selected using the criteria of location (altitude) and dairy organisation (whether Village Dairy Cooperative or not) in 4 different Community Development Blocks in the 2 milk sheds of Almora and Nainital brings to the fore a clear picture of the dairy farms. Almost all the smallholder dairy farms practise sedentary management, in which livestock, supplemented with daytime grazing, are kept in a viilage throughout the year. Dairy-manure with buffalo and dairy-manure-draught power with cattle are the 2 main types of dairy farms with an overwhelming presence of mixed ones, i.e., involving cattle and buffaloes throughout the study area. Among cattle, 93% are indigenous. Fresh whole milk is the most common of the unprocessed dairy products sold by farmers. Most of the inputs in smallholder dairy are internally mobilised. Common property resources and cropland are the 2 sources oflivestock feed in the area. In contrast, most market-oriented dairy farms in the Village Dairy Cooperatives (VDCs) purchase feed for their dairy animals. An overwhelming majority of smallholder dairy farms operates in small and medium scale of production (45 and 57%) respectively. Only 8% farms in the sample villages witnessed large production scale. Percentage of smallholders managing medium and large-scale dairy production is higher in the VDCs and in the villages located near urban area suggesting a little more scope of higher income through milk sale. Many of the specific cilaracteristics of a dairy farm depend upon the location. The dismal state of the livestock feeding in the area is that the requirement in each village is far more than the actual availability offooder. Average shortage of green fodder is 26% and that of dry fodder as high as 77%. This situation, obviously, becomes the major reason for poor performance of livestock in the region. Dairying is one of the most important dimensions of diversified mountain agriculture to reduce risks and derive more economic benefits from the limited resource base. Owing to the CRPs regime in the region, dairy ought to be one of the most potential and attractive economic activities for the majority of smallholders in the mountains.